Anthropometric variables in standing posture in a population of male and female workers in Latin America: a systematic search. - Labrador Parra, Alejandro (Conexiones UG, 2025)
Anthropometry plays a fundamental role in public health since it takes advantage of anthropometric data for the design of the workplace and personal protective equipment (PPE), which are key within the work environment; however, there are few studies on respect in Latin America. The methodology used was a systematic review of the standing anthropometric variables in a population of workers in Latin America, between May and October 2024. Of the results obtained, 3485 cases or related studies were reviewed. with anthropometry in the industrial environment and nine (9) were selected, who were those who met the inclusion and exclusion schemes, which gave an approximation or important contributions in this research in the prosecution of anthropometric studies that allow the design of jobs and improvement in terms of health and welfare of workers.